Diagnostic performance of digital tomosynthesis for postoperative assessment of acetabular fractures and pelvic ring injuries - Coscia, Atticus; Schweppe, Eric; Anari, Jason; Kneeland, Bruce; Horan, Annamarie; Mehta, Samir; Ahn, Jaimo (Frontiers in Surgery, 2024)
IntroductionDigital tomosynthesis (DTS) has broad non-orthopaedic applications and has seen limited use within orthopaedics for imaging of the wrist. The utility of DTS for assessing reduction and hardware placement following operative treatment of pelvic ring injuries and acetabular fractures has not previously been investigated.MethodsAll operatively treated acetabular fractures and pelvic ring injuries that underwent surgical fixation within a one-year time span received both a computed tomography (CT) scan and a DTS scan as part of their routine postoperative imaging workup. Three orthopaedic traumatologists independently reviewed the images for face-value clinical utility. Radimetrics and PCXMC software were utilized on a subset of the study population's DTS and CT studies to calculate the effective and organ radiation doses delivered.Results52 patients (22 acetabular fractures, 22 pelvic ring injuries, 7 pelvic ring and acetabular fractures, 2 femoral head & acetabular fractures) were included. DTS was considered adequate to assess reduction 83% of the time, hardware position 83% of the time, and sufficient to replace the CT scan 67% of the time. DTS was associated with an 8.3 times lower effective radiation dose than CT. All organ doses were lower for DTS than CT.DiscussionDTS appears to have face-value clinical utility for assessing reduction and hardware position following surgical treatment of acetabular fractures and pelvic ring injuries. Given that DTS is associated with significantly lower radiation doses to patients, further study utilizing more objective criteria is warranted.